'Roots-searching' and contemporary landscape photography in China. Issue 3 (2nd September 2019) - Yang, Yunchang
Abstract : This article aims to discuss a discursive turn of Chinese visual arts, using landscape representations from old and contemporary photographs of China, as well as painting and film materials. The discussion starts from showing the differences of defining the term landscape between Western and Chinese painters, arguing that they point to two types of realism underpinned by two kinds of cultures of seeing. It then moves on to the anthropological analysis of the landscape and how this analytical framework is useful in terms of understanding the 'emotive reality' in traditional Chinese landscape paintings. Lastly, the essay attempts to point out that this legacy has been inherited by contemporary Chinese visual arts in form of a 'roots-searching' sentimentality, either in explicit or implicit ways, participating in the construction of the new reality and identity recognised by and shapes contemporary Chinese artists.